Corpus Study of the Adverb of Degree ‘Feichang’ in Chinese and English Parallel Corpus - Clara Herlina Karjo; Mei Rianto Chandra (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
The use of a parallel corpus for Chinese and English adverbs is still rarely explored, especially when comparing the Chinese adverb feichang with its English equivalents. ‘Feichang’ literally means